2006
DOI: 10.22358/jafs/66933/2006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding regular or low α-linolenic acid linseed on the fatty acid composition of egg yolks

Abstract: Ninety Isa Brown laying hens aged 28 weeks, kept in individual cages, were randomly divided into 6 groups of 15 birds each. Six isoproteinous diets differing in crude fat content and fatty acid (FA) composition were prepared. The source of added fat was linseeds (50 g/kg diet), regular cultivars (Omega and Opal) with a high content of α-linolenic acid (HA), or a modified cultivar (Linola) with low α-linolenic acid-and high linoleic acid (LA) contents, soyabean oil, or LA linseed oil (20 g/kg diet). The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
3
10
1
Order By: Relevance
“…Grobas et al (2001) showed that laying hens fed a diet containing 5% or 10% linseed oil during 12 weeks trial period produced eggs with the same yolk weights, egg weight and egg mass as control birds. The same results were reported by Beynen (2004) and Sosin et al (2006) on the yolk weight, but not the egg weight. They revealed that egg weight decreased significantly (P <0.05) by feeding linseed to the hens.…”
Section: Discussionsupporting
confidence: 88%
“…Grobas et al (2001) showed that laying hens fed a diet containing 5% or 10% linseed oil during 12 weeks trial period produced eggs with the same yolk weights, egg weight and egg mass as control birds. The same results were reported by Beynen (2004) and Sosin et al (2006) on the yolk weight, but not the egg weight. They revealed that egg weight decreased significantly (P <0.05) by feeding linseed to the hens.…”
Section: Discussionsupporting
confidence: 88%
“…The fatty acid profile of eggs is highly dependent on the diet of laying hens (Yannakopoulos et al, 2005;Sosin et al, 2006). The present study demonstrates that MUFA tended to increase with increasing levels of dietary glycerol, but this increase was not significant.…”
Section: Supplemental Glycerol Performance Laying Henscontrasting
confidence: 39%
“…These results are consistent with the findings of Scheideler et al (1998), Novak & Scheideler (2001), and Bean & Leeson (2003), who reported no change in these egg characteristics in layers fed diets containing linseed. On the other hand, Baynen (2004), and Sosin et al (2006) reported that feeding layers with linseed reduced (p ≤ 0.05) egg weight, while yolk weight remained constant. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sosin et al (2006) also indicated reduced egg weight when layers were fed linseed. Bean & Leeson (2003) found yolk weight reduction in layers consuming linseed, whereas Sosin et al (2006) reported that feeding linseed to layers had no effect on the yolk weight. Considering these contradictory results, the effects of linseed feeding on layer performance needs to be further evaluated.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation